The Digital Reading Desk: A lightweight approach to digital note-taking - Jen Pearson (Interacting with Computers, 2012)
Attentive reading is a complex and cognitively demanding task that uses note-taking and annotation to support the reader’s interpretation of the document. When reading on paper, extensive use of highlighting and other activities are conducted to support attentive reading, but this rich behaviour is not used with digital documents. Many users therefore print digital documents and then interact with them in physical form.This paper presents the “Digital Reading Desk,” an enhanced digital reading environment that provides support for attentive reading, providing a large working space for notes that mimics the use of desk space in a conventional physical environment. The Reading Desk uses a single tool to support both annotation and bookmarking, simplifying both the user’s learning of the system and their use of tools. Evaluation of the Reading Desk indicates preference for it, as well as considerable behavioural differences between our approach and traditional digital reading tools.